Synthesis and investigation of new cholesteryl carbamate-based liquid crystals - Korkmaz, Burak; Kirsoy, Ahmet; Okutan, Mustafa; Gursel, Yesim; Senkal, Bahire Filiz (SPRINGER, 2022)
Cholesteryl chloroformate which is known liquid crystal material was modified to give the new molecules a long-lasting LC phases with the stability of the carbamate and aromatic functions. Two new mesogens cholesteryl 1H-imidazole-1-carboxylate (Cho-Imi) and Cholesteryl (4-((E)-phenyldiazenyl) phenyl) carbamate (Cho-Diazo) were synthesized starting from Cholesteryl chloroformate and (E)-4-(phenyldiazenyl) aniline in the presence of triethylamine (TEA) as an acid scavenger at room temperature. Structural characterization of the obtained LC compounds was performed by FTIR and H-NMR. These new compounds, which show more than one LC phase different from the LC phases of the starting material, showed that they are promising as a result of the analyses. The mesomorphic properties were examined by polarized optical microscope (POM) and thermal properties of the LC compounds were determined by DSC and TGA. The dielectric properties of synthesized liquid crystal samples were investigated using dielectric spectroscopy technique. It was seen that both new syntheses mesogen cholesteryl carbamates-based liquid crystal samples exhibit non-Debye type relaxation properties. The cole-cole analysis by dielectric spectroscopy was used to determine the equivalent devices of this new Cholesteryl carbamate-based mesogens. The samples have different dielectric properties in different frequency regions will provide significant flexibility as a working frequency region in engineering, biological and genetic application areas.
Keywords: ORGANIC MATERIALS; BEHAVIOR; DERIVATIVES; RELAXATION; DISPERSION; HYDROGELS; FOOD; Engineering; Materials Science; Physics